Cell Specific Changes of Autophagy in a Mouse Model of Contusive Spinal Cord Injury - Muñoz-Galdeano, Teresa; Reigada, David; del Águila, Ángela; Velez, Irene; Caballero-López, Marcos J.; Maza, Rodrigo M.; Nieto-Díaz, Manuel (Frontiers in Cellular Neuroscience, 2018)
Autophagy is an essential process of cellular waist clearance that becomes altered following spinal cord injury (SCI). Details on these changes, including timing after injury, underlying mechanisms, and affected cells, remain controversial. Here we present a characterization of autophagy in the mice spinal cord before and after a contusive SCI. In the undamaged spinal cord, analysis of LC3 and Beclin 1 autophagic markers reveals important differences in basal autophagy between neurons, oligodendrocytes, and astrocytes and even within cell populations. Following moderate contusion, western blot analyses of LC3 indicates that autophagy increases to a maximum at 7 days post injury (dpi), whereas unaltered Beclin 1 expression and increase of p62 suggests a possible blockage of autophagosome clearance. Immunofluorescence analyses of LC3 and Beclin 1 provide additional details that reveal a complex, cell-specific scenario. Autophagy is first activated (1 dpi) in the severed axons, followed by a later (7dpi) accumulation of phagophores and/or autophagosomes in the neuronal soma without signs of increased initiation. Oligodendrocytes and reactive astrocytes also accumulate phagophores and autophagosomes at 7 dpi, but whereas the accumulation in astrocytes is associated with an increased autophagy initiation, it seems to result from a blockage of the autophagic flux in oligodendrocytes. Comparison with previous studies highlights the complex and heterogeneous autophagic responses induced by the SCI, leading in many cases to contradictory results and interpretations. Future studies should consider this complexity in the design of therapeutic interventions based on the modulation of autophagy to treat SCI.